Electrolyte preparation method
Lithium sulfide is synthesized by carbon thermal reduction method and pre-alloyed with lithium chloride and diphosphorus pentasulfide. Finally, the electrolyte is obtained through sintering, which solves the problem of stable circulation of lithium-ion batteries and high energy consumption of high-purity lithium sulfide synthesis, and realizes the stability of the interface contact between the electrolyte and the positive electrode of the oxide and the stable circulation of the battery.
Patent Information
- Application Number
- CN202310070421.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-01-17
AI Technical Summary
The stable circulation of existing lithium-ion batteries is affected by the interface reaction of sulfide solid electrolyte and oxide positive electrode, and the synthesis method of high purity lithium sulfide has problems of high energy consumption and high production costs.
Lithium sulfide is synthesized by carbon thermal reduction method, and pre-alloyed with lithium chloride and diphosphorus pentasulfide. Finally, the electrolyte is obtained through sintering, and the molar ratio of lithium sulfide, diphosphorus pentasulfide and lithium chloride is regulated to synthesize lithium phosphate in situ to form a composite electrolyte.
The stability of the interface contact between the electrolyte and the oxide positive electrode is enhanced, the stable circulation of lithium-ion all-solid state batteries is realized, and the energy consumption and cost of electrolyte production is reduced.
Smart Images

Figure CN116002724B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrolytes, and in particular relates to a solid electrolyte for a lithium-ion all-solid-state battery. Background Art
[0002] The synthesis of existing sulfide solid electrolytes uses high-purity lithium sulfide (i.e., purity > 99.9%) as raw material. The main methods for synthesizing lithium sulfide include mechanical ball milling, high temperature and high pressure, solvent reaction, and carbon thermal reduction. However, none of these four methods can directly synthesize high-purity lithium sulfide. It must be dissolved, filtered, evaporated, and recrystallized with an alcohol solvent. However, this step greatly increases the energy consumption for manufacturing lithium sulfide and the production cost of the electrolyte. In addition, the synthesized electrolyte has a strong interface reaction with the oxide positive electrode and does not utilize the stable cycle of the battery.
[0003] In order to fundamentally solve the problem of stable circulation of lithium-ion batteries, lithium sulfide (purity>85%) is directly synthesized by carbon thermal reduction method. Its main by-product is lithium carbonate. Lithium sulfide containing lithium carbonate does not need to be purified by dissolution, filtration, evaporation and recrystallization using alcohol solvents, and can be directly used for the synthesis of electrolytes. By adjusting the molar ratio of lithium sulfide, phosphorus pentasulfide and lithium chloride, lithium phosphate is synthesized in situ while synthesizing the sulfide solid electrolyte. Lithium phosphate acts as a fast ion conductor and forms a composite electrolyte with the sulfide solid electrolyte. The ion conductivity of the obtained electrolyte reaches more than 3.5mS / cm. At the same time, due to the presence of oxides in the electrolyte, the stability of the interface contact between the electrolyte and the oxide positive electrode can be enhanced. The all-solid-state battery assembled using this electrolyte can achieve stable circulation. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing an electrolyte, wherein lithium sulfide is synthesized by a carbon thermal reduction method, and pre-alloyed with lithium chloride and phosphorus pentasulfide, and finally the electrolyte obtained by sintering can enhance the stability of the electrolyte and the oxide positive electrode interface contact.
[0005] Another object of the present invention is to provide a battery, wherein the electrolyte prepared by the above method is filled between the positive electrode sheet and the negative electrode sheet to achieve stable circulation.
[0006] In order to achieve the above-mentioned first object, the present invention provides a method for preparing an electrolyte, characterized in that it comprises the steps of:
[0007] Adding lithium sulfate and a carbon material to mix to form a mixture;
[0008] Carbothermal reduction is performed on the mixture to form lithium sulfide;
[0009] Pre-alloying the lithium sulfide with lithium chloride and phosphorus pentasulfide to produce an electrolyte mother powder; and
[0010] The electrolyte mother powder is sintered to produce an electrolyte.
[0011] Preferably, the lithium carbonate content in the lithium sulfide is 0%-15%.
[0012] Preferably, the purity of the lithium sulfide is 85%-100%.
[0013] Preferably, the molar ratio of the lithium sulfide to the phosphorus pentasulfide is 5:1.01 to 5:1.1, and the molar ratio of the lithium sulfide to the lithium chloride is 5:2.
[0014] Preferably, the ratio of lithium sulfate to carbon material is 1:1.5 to 1:2.5.
[0015] Preferably, the carbon material is at least one of an organic carbon source and an inorganic carbon source.
[0016] Preferably, when the carbon material is an organic carbon source, the ratio of the lithium sulfate to the carbon material is 1:2 to 1:2.5, and when the carbon material is an inorganic carbon source, the ratio of the lithium sulfate to the carbon material is 1:1.5 to 1:2.
[0017] Preferably, in the step of adding lithium sulfate and a carbon material to form a mixture, the lithium sulfate and the carbon material are mixed by a wet ball milling process.
[0018] Preferably, a medium of the wet ball milling process is at least one of methanol, ethanol and ethylene glycol, and the ball milling speed of the wet ball milling process is 150rpm-1000rpm, the ball-to-material ratio is 5:1 to 40:1, and the ball milling time is 1h-160h.
[0019] Preferably, in the step of pre-alloying the lithium sulfide, lithium chloride and phosphorus pentasulfide to produce an electrolyte mother powder, the lithium sulfide, lithium chloride and phosphorus pentasulfide are pre-alloyed by a dry ball milling process.
[0020] Preferably, the ball milling speed of the dry ball milling process is 150 rpm-1000 rpm, the ball-to-material ratio is 5:1 to 40:1, and the ball milling time is 1 h-160 h.
[0021] Preferably, in the step of sintering the electrolyte mother powder to produce an electrolyte, the sintering temperature is 800° C.-1000° C., and the sintering time is 1 h-15 h.
[0022] Preferably, in the step of sintering the electrolyte mother powder to produce an electrolyte, the electrolyte mother powder is placed in a muffle furnace for sintering, and the sintering temperature is 400° C.-750° C., and the sintering time is 0.25 h-15 h.
[0023] Preferably, the electrolyte comprises a LPSC and a lithium phosphate, the LPSC content accounts for 85%-100%, the lithium phosphate content accounts for 0%-15%, and the ion conductivity of the electrolyte is greater than 3.5 mS / cm.
[0024] In order to achieve the above first object, the present invention provides a battery, characterized in that it includes:
[0025] a positive electrode;
[0026] a negative electrode; and
[0027] An electrolyte, such as the electrolyte described above, is filled between the positive electrode sheet and the negative electrode sheet, so that the positive electrode sheet is electrically connected to the negative electrode sheet.
[0028] The beneficial effects of the present invention are that the electrolyte prepared therefrom can enhance the stability of the interface contact between the electrolyte and the oxide positive electrode, and the all-solid-state battery constructed therefrom can achieve stable circulation, thereby improving the conventional deficiencies. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a flow chart of a method for preparing an electrolyte according to an embodiment of the present invention;
[0030] Figure 2 A schematic diagram of the structure of a battery according to an embodiment of the present invention
[0031] Figure 3 is an XRD diagram of lithium sulfide and electrolyte according to an embodiment of the present invention; and
[0032] Figure 4 This is a graph showing the ionic conductivity results of different lithium sulfide synthetic electrolytes according to an embodiment of the present invention. DETAILED DESCRIPTION
[0033] In order to make the above and / or other purposes, effects, and features of the present invention more clearly understood, preferred embodiments are specifically described below in detail:
[0034] See also Figure 1 , which is a flow chart of a method for preparing an electrolyte according to an embodiment of the present invention. As shown in the figure, in one embodiment, the method for preparing an electrolyte comprises the following steps:
[0035] Step S1: adding lithium sulfate and a carbon material to form a mixture;
[0036] Step S2: performing a carbothermal reduction reaction on the mixture to form lithium monosulfide;
[0037] Step S3: pre-alloying the lithium sulfide with lithium chloride and phosphorus pentasulfide to produce an electrolyte mother powder; and
[0038] Step S4: sintering the electrolyte mother powder to produce an electrolyte.
[0039] As shown in step S1, lithium sulfate and carbon material are fully mixed by wet ball milling to form a mixture according to weight parts, wherein the medium of the wet ball milling process is at least one of methanol, ethanol, and ethylene glycol, and the ball milling speed of the wet ball milling process is 150rpm-1000rpm, the ball-to-material ratio is 5:1 to 40:1, the ball milling time is 1h-160h, and the ratio of lithium sulfate to carbon material is 1:1.5 to 1:2.5. Preferably, the carbon material is at least one of an organic carbon source and an inorganic carbon source. When the carbon material is an organic carbon source, the ratio of lithium sulfate to carbon material is 1:2 to 1:2.5, wherein the organic carbon source includes but is not limited to organic matter that can be carbonized at high temperature, such as glucose, sucrose, and starch. When the carbon material is an inorganic carbon source, the ratio of lithium sulfate to carbon material is 1:1.5 to 1:2, wherein the inorganic carbon source includes but is not limited to inorganic matter that can be directly used as a carbon source, such as graphite, activated carbon, graphene, carbon nanotubes, and acetylene black.
[0040] As shown in step S2, the mixture formed in the previous step is subjected to a carbon thermal reduction reaction to form lithium sulfide. In one embodiment, in addition to the main reaction other than equation 1, a side reaction shown in equation 2 also occurs during the carbon thermal reduction process to synthesize lithium sulfide, thereby obtaining an intermediate by-product, lithium oxide (Li2O). Li2O reacts with carbon dioxide (CO2) produced by the main reaction to produce a final by-product, lithium carbonate (as shown in equation 3), wherein the content of lithium carbonate in the lithium sulfide is controlled by the sintering process, and the content of lithium carbonate in the lithium sulfide is 0%-15%, and the purity of the lithium sulfide is 85%-100%.
[0041] Equation 1: Li2SO4+2C=Li2S+2CO2(g)
[0042] Equation 2: Li2SO4+1.5C=Li2O+1.5CO2(g)+S
[0043] Equation 3: Li2O+CO2(g)=Li2CO3
[0044] As shown in step S3, the lithium sulfide formed in the previous step is pre-alloyed with lithium chloride and phosphorus pentasulfide by dry ball milling to produce electrolyte mother powder, wherein the ball milling speed of the dry ball milling process is 150 rpm-1000 rpm, the ball-to-material ratio is 5:1 to 40:1, and the ball milling time is 1h-160h. In one embodiment, lithium sulfide and phosphorus pentasulfide (P4S 10) is 5:1.01 to 5:1.1, and the molar ratio of lithium sulfide to lithium chloride is 5:2. Preferably, phosphorus pentasulfide increases with the increase of lithium carbonate content. The reason for the excess of phosphorus pentasulfide is that phosphorus pentasulfide can react with the by-product lithium carbonate as shown in Equation 4 to generate lithium sulfide and lithium phosphate (Li3PO4). Lithium phosphate forms a composite solid electrolyte as an oxide fast ion conductor and a sulfide fast ion conductor.
[0045] Equation 4: 8Li2CO3+P2S5=2Li3PO4+5Li2S+8CO2(g)
[0046] As shown in step S4, the electrolyte mother powder produced in the previous step is subjected to a sintering procedure to produce an electrolyte, wherein the sintering temperature is 800°C-1000°C, and the sintering time is 1h-15h. Preferably, the electrolyte mother powder is placed in a muffle furnace in a glove box (water and oxygen contents are all less than 0.1ppm) for sintering, and the sintering temperature is 400°C-750°C, and the sintering time is 0.25h-15h. The final electrolyte produced contains LPSC and lithium phosphate, and the LPSC content accounts for 85%-100%, the lithium phosphate content accounts for 0%-15%, and the ionic conductivity of the produced electrolyte is greater than 3.5mS / cm, thereby enhancing the stability of the interface contact between the electrolyte and the oxide positive electrode.
[0047] In one embodiment, see Figure 2 , which is a schematic diagram of the structure of a battery according to one embodiment of the present invention. As shown in the figure, in one embodiment, the battery 1 includes a positive electrode sheet 11, a negative electrode sheet 12, and an electrolyte 13, and the electrolyte 13 is filled between the positive electrode sheet 11 and the negative electrode sheet 12, so that the positive electrode sheet 11 and the negative electrode sheet 12 are electrically connected through the electrolyte 13.
[0048] Please also refer to Table 1, which shows the refined results of electrolytes synthesized using different lithium sulfides.
[0049]
[0050] In summary, it can be seen from the data results in Table 1 that the ionic conductivity of Examples 1-6 of the present application and the synthesis temperature and synthesis time of lithium sulfide indicate that in the electrolyte prepared by one embodiment of the present invention, lithium carbonate appears while synthesizing the electrolyte, and the lithium carbonate is converted into lithium phosphate in the subsequent step. Moreover, the purpose of synthesizing the electrolyte in one embodiment of the present invention is to synthesize a pure phase LPSC electrolyte, that is, an LPSC electrolyte with a purity of 100%. However, when synthesizing lithium sulfide, lithium carbonate will appear, and the lithium carbonate will be converted into lithium phosphate in the process of synthesizing the electrolyte, that is, lithium phosphate is a by-product in the LPSC electrolyte. Therefore, this lithium phosphate is used as a fast ion conductor, that is, a solid electrolyte.
[0051] Depend on Figure 3 It can be seen that this is an XRD diagram of lithium sulfide and electrolyte in one embodiment of the present invention. As shown in the figure, the XRD diagrams of lithium sulfide and electrolyte at different sintering temperatures and sintering times show that lithium sulfide definitely contains lithium carbonate, and the electrolyte definitely contains lithium phosphate, which is a mutually corroborating relationship with Table 1.
[0052] Depend on Figure 4 It can be seen that this is a graph showing the ionic conductivity results of different lithium sulfide synthetic electrolytes in one embodiment of the present invention. As shown in the figure, the performance of the electrolyte directly affects the capacity, operating temperature, safety and cycle performance of the lithium-ion battery. The ionic conductivity of the organic electrolyte at room temperature can reach 10 -3 S / cm to 10 -2 S / cm, so in order to meet the use requirements, the ionic conductivity of the solid electrolyte at room temperature should be more than 10 -4 S / cm. In one embodiment, the ionic conductivity of the synthesized electrolyte exceeds 3.4×10 -3 S / cm.
[0053] In summary, the content of LPSC and lithium phosphate is the content of pure phase and useful byproducts, and the prepared electrolyte can enhance the stability of the electrolyte and oxide positive electrode interface contact, among which Rwp and χ 2 To prove the credibility of data refinement, Rwp and χ 2 The smaller the value, the more accurate the refinement result. When the value is less than 10, the credibility of the result can be guaranteed, and the all-solid-state battery constructed therewith can achieve stable circulation, thereby achieving the purpose of the present invention.
[0054] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art may make several improvements and modifications without departing from the concept of the present invention, and these improvements and modifications should also be regarded as within the scope of the present invention.
Claims
1. A method for preparing an electrolyte, characterized in that: Includes steps: Adding lithium sulfate and a carbon material to mix to form a mixture, wherein the ratio of the lithium sulfate to the carbon material is 1:1.5 to 1:2.5; Carbothermal reduction is performed on the mixture to form lithium sulfide, wherein the lithium carbonate content in the lithium sulfide is 0%-15% but not 0%; Pre-alloying the lithium sulfide with lithium chloride and phosphorus pentasulfide to produce an electrolyte mother powder; and The electrolyte mother powder is sintered to produce an electrolyte, wherein the electrolyte comprises an LPSC and a lithium phosphate, and the ion conductivity of the electrolyte is greater than 3.5 mS / cm.
2. The method for preparing the electrolyte according to claim 1, characterized in that: The purity of the lithium sulfide is 85%-100% but not 100%.
3. The method for preparing the electrolyte according to claim 1, characterized in that: The molar ratio of the lithium sulfide to the phosphorus pentasulfide is 5:1.01 to 5:1.1, and the molar ratio of the lithium sulfide to the lithium chloride is 5:
2.
4. The method for preparing the electrolyte according to claim 1, characterized in that: The carbon material is at least one of an organic carbon source and an inorganic carbon source.
5. The method for preparing the electrolyte according to claim 4, characterized in that: When the carbon material is an organic carbon source, the ratio of lithium sulfate to carbon material is 1:2 to 1:2.5; when the carbon material is an inorganic carbon source, the ratio of lithium sulfate to carbon material is 1:1.5 to 1:
2.
6. The method for preparing the electrolyte according to claim 1, characterized in that: In the step of adding lithium sulfate and a carbon material to form a mixture, the lithium sulfate and the carbon material are mixed by a wet ball milling process.
7. The method for preparing the electrolyte according to claim 6, characterized in that: A medium of the wet ball milling process is at least one of methanol, ethanol, and ethylene glycol, and the ball milling speed of the wet ball milling process is 150rpm-1000rpm, the ball-to-material ratio is 5:1 to 40:1, and the ball milling time is 1h-160h.
8. The method for preparing the electrolyte according to claim 1, characterized in that: In the step of pre-alloying the lithium sulfide, lithium chloride and phosphorus pentasulfide to produce an electrolyte mother powder, the lithium sulfide, lithium chloride and phosphorus pentasulfide are pre-alloyed by a dry ball milling process.
9. The method for preparing the electrolyte according to claim 8, characterized in that: The dry ball milling procedure has a ball milling speed of 150 rpm to 1000 rpm, a ball-to-material ratio of 5:1 to 40:1, and a ball milling time of 1 h to 160 h.
10. The method for preparing the electrolyte according to claim 1, characterized in that: In the step of sintering the electrolyte mother powder to produce an electrolyte, the sintering temperature is 800° C.-1000° C., and the sintering time is 1 h-15 h.
11. The method for preparing the electrolyte according to claim 1, characterized in that: In the step of sintering the electrolyte mother powder to produce an electrolyte, the electrolyte mother powder is placed in a muffle furnace placed in a glove box for sintering, and the sintering temperature is 400° C.-750° C., and the sintering time is 0.25h-15h.
12. The method for preparing the electrolyte according to claim 1, characterized in that: The LPSC content accounts for 85%-100% but not 100%, and the lithium phosphate content accounts for 0%-15% but not 0%.
13. A battery, characterized in that: include: a positive electrode; a negative electrode; and An electrolyte, as claimed in any one of claims 1 to 12, is filled between the positive electrode sheet and the negative electrode sheet, so that the positive electrode sheet is electrically connected to the negative electrode sheet.
Citation Information
Patent Citations
Electrolyte material for all solid-state lithium secondary battery, preparation method for electrolyte material and all solid-state lithium secondary battery
CN103560267A
Manufacturing method of lithium sulfide and manufacturing method of inorganic solid electrolyte
JP2016216349A